2018
DOI: 10.21271/zjpas.30.s1.14
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and potential treatment technologies for different kinds of wastewaters

Abstract: The current work was aimed to characterize and defining appropriate treatment processes for various types of raw wastewaters. The fresh wastewater samples were collected from slaughterhouse (SWW), tannery (TWW), municipal (MWW), municipal landfill leachate (MLL), and dairy (DWW). The collected samples were analyzed for temperature, pH, electrical conductivity, turbidity, total alkalinity, total hardness, biological and chemical oxygen demands, suspended and dissolved solids etc. Commonly, MLL contained low bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…From the documented data, parameters such as pH, temperature, and chloride were in accordance with the standards for wastewater disposal, while TSS and BOD5 exceeded the standards (Mustafa and Sabir 2001;Ali, 2002;Aziz, 2004;Shekha, 2008;Aziz and Ali, 2017;Aziz, 2020). In the literature, wastewater samples were analyzed at another site in Erbil City and some parameters such as BOD5, COD, ammonia, manganese, phenols, oil and grease, TS, TSS and TDS exceeded the standards for wastewater disposal (Aziz and Ali, 2017;2018). Therefore, treatment of wastewater in Erbil city was proposed using different methods such as aerated lagoon, oxidation pit and wetland for wastewater reuse.…”
Section: Ww Characteristicsmentioning
confidence: 65%
See 1 more Smart Citation
“…From the documented data, parameters such as pH, temperature, and chloride were in accordance with the standards for wastewater disposal, while TSS and BOD5 exceeded the standards (Mustafa and Sabir 2001;Ali, 2002;Aziz, 2004;Shekha, 2008;Aziz and Ali, 2017;Aziz, 2020). In the literature, wastewater samples were analyzed at another site in Erbil City and some parameters such as BOD5, COD, ammonia, manganese, phenols, oil and grease, TS, TSS and TDS exceeded the standards for wastewater disposal (Aziz and Ali, 2017;2018). Therefore, treatment of wastewater in Erbil city was proposed using different methods such as aerated lagoon, oxidation pit and wetland for wastewater reuse.…”
Section: Ww Characteristicsmentioning
confidence: 65%
“…forest, greenbelt, wheat, fruits, vegetables, etc. (Mecalf and Eddy, 2014;Aziz and Ali, 2018;Aziz et al, 2019). Three key views should be measured for irrigation by treated WW, which cares about public health for farmers and users, the avoidance of atmosphere degradation, and removes the antagonistic that has an effect on the production of crops.…”
Section: Reusing Treated Municipal Ww For Irrigationmentioning
confidence: 99%
“…The increase in pH value may be related to changes in the relationship between carbon dioxide, alkalinity, and pH due to algae consuming inorganic carbon dioxide from the underwater environment. In general, the pH value is still within irrigation water quality standards [6,19]. In addition, chloride concentration is between 16 to 94 mg/L and the removal percentage is (2.5 -82.98%) after reed beds.…”
Section: Wastewater Samples Characteristics and Natural Treatment Usi...mentioning
confidence: 97%
“…They found that EMWW is proper for cooked vegetables and for irrigating green area [19]. Also, Aziz et al [6] investigated on fresh WW samples had been gathered from Yörüksüt Dairy Factory and Erbil Steel Company and evaluated for 21 water pleasant parameters like COD, BOD5, TSS, etc. were surpassed the standards for removal of WW.…”
Section: Reusing Of Treated Municipal Wastewatermentioning
confidence: 99%
See 1 more Smart Citation